Clinical and video-polysomnographic analysis of rapid eye movement sleep behavior disorder and other sleep disturbances in dementia with Lewy bodies - Fernández-Arcos, Ana; Morenas-Rodríguez, Estrella; Santamaria, Joan; Sánchez-Valle, Raquel; Lladó, Albert; Gaig, Carles; Lleó, Alberto; Iranzo, Alex (Sleep (New York, N.Y.), 2019)
The main objective of this study was to study rapid eye movement (REM) sleep behavior disorder (RBD) and other sleep disorders in dementia with Lewy bodies (DLB). Consecutive patients with DLB and mild dementia severity were recruited irrespective of sleep complaints. Patients underwent clinical interview, assessment of sleep scales, and video-polysomnography (V-PSG). RBD was diagnosed with V-PSG based on electromyographic and audiovisual analysis. Thirty-five patients (65.7% men; mean age 77.7 ± 6.1 years) were evaluated. Poor sleep quality (54.3%), hypersomnia (37.1%), snoring (60%), and abnormal nocturnal behaviors (77.1%) were reported. Sleep-wake architecture abnormalities occurred in 75% patients and consisted of occipital slowing on awake electroencephalography (EEG; 34.4%), the absence of sleep spindles and K complexes (12.9%), slow frequency sleep spindles (12.9%), delta activity in REM sleep (19.2%), and REM sleep without atonia (44%). Three patients showed hallucinatory-like behaviors and 10 patients showed abnormal behaviors during arousals mimicking RBD. RBD was diagnosed in 50% of those patients in whom sufficient REM sleep was attained. Of these, 72.7% were not aware of displaying dream-enacting behaviors and in 63.7% RBD preceded the onset of cognitive impairment. For RBD diagnosis, the sensitivity of Mayo Sleep Questionnaire was 50%, specificity was 66.7%, positive predictive value was 83.3%, and negative predictive value was 28%. False-positive RBD cases according to clinical history had hallucinatory-like behaviors, severe obstructive sleep apnea, and prominent periodic limb movements in sleep. Occipital EEG frequency while awake and rate of electromyographic activity in REM sleep were negatively correlated, suggesting a common subcortical origin. In DLB, RBD and sleep-wake disorders are common, heterogeneous, and complex, challenging their identification without performing V-PSG.